Research portfolio - Hoveka, E P (Rhodes University, Faculty of Education, Department of Education, 2004)
The purpose of this study is to look at English Second Language IGCSE Core Curriculum for Grades 11 and 12. The criteria that has been identified and selected for analysis as stipulated by the Ministry of Basic Education and Culture Language policy Document of 1996 reads as follows: The aim of teaching English as a language should be to enable the learners to increase their participation in the learning processes. This aim was selected as the criteria for investigation because the notion of active participation by the learners in the teaching and learning process places the learners in a different perspective. In other words, the learners are to be seen as possessors of knowledge rather than 'empty vessels' as depicted by the behaviourist approach (Van Harmelen 1999). This idea of a learner-centred approach as embedded in Social Constructivism approach is the foundation on which the Namibian Education Reform Process is based. The justification for selecting these particular criteria for close inspection in the English Second Language Curriculum was sparked by the professional attachment of the researcher into teaching English Second Language to Grades 11 and 12 at the Herman Gmeiner Technical School in Swakopmund. The researcher is also serving as a subject head for this particular discipline. Furthermore, evaluating and analyzing the English Second Language curriculum on this particular objective, the researcher hopes to uncover or come to an understanding of how our educational practices have moved from what was practiced under the behavioural approach and to discover the needs of teachers in terms of implementing the new curriculum in their daily practices as educators. Having the criteria stated, the study will focus on how the data was collected and the type of methodology used to gather this information.
Keywords: Education -- Namibia; Teaching -- Namibia; Curriculum planning -- Namibia; Educational change -- Namibia; English language -- Study and teaching (Secondary) -- Namibia